JWST/NIRCam observations of stars and H ii regions in z ≃ 6–8 galaxies: properties of star-forming complexes on 150 pc scales. Issue 4 (29th November 2022) - Chen, Zuyi; Stark, Daniel P; Endsley, Ryan; Topping, Michael; Whitler, Lily; Charlot, Stéphane
ABSTRACT: The onset of the JWST -era provides a much-improved opportunity to characterize the resolved structure of early star-forming systems. Previous Spitzer observations of z ≳ 6 galaxies revealed the presence of old stars and luminous H ii regions (via [O iii ]+H β emission), but the poor resolution stunted our ability to map their locations with respect to the star-forming regions identified in the rest-UV. In this paper, we investigate the internal structure of 12 of the most luminous z ≃ 6–8 galaxies in the EGS field observed with recent JWST /NIRCam imaging. The systems appear clumpy in the rest-UV, with more than half of the light coming from ≃ 10 7 to 10 9 M⊙ star-forming complexes that are ≃150–480 pc in size. The clumps tend to be dominated by young stars (median = 36 Myr), but we also find large variations in clump ages within individual galaxies. The [O iii ]+H β EW varies significantly across individual galaxies (reflecting differences in stellar and gas properties), but the H ii regions largely track the UV-bright complexes. Perhaps surprisingly, the rest-optical continuum is just as clumpy as the UV, and we do not find older (and redder) nuclear stellar components that were previously undetected or faint in the UV. The majority of the stellar mass in bright 6 < z < 8 galaxies appears to be contained in the ≳150 pc-scale clumpy star-forming complexes, reflecting the very active phase of assembly that is common in reionization-era galaxies.